Purulent Streptococcus pneumoniae meningoencephalitis in adults in Casablanca - Dr Hassan Kamena Mwana-yile Mwana-yile; Professor Fatima IHBIBANE; Dr Ouiame ELFADEL; Professor Batubenga Hydrice KAYIMBI; Professor Bosonga Raissa BONGUNGU; Professor Latifa MARIHI; Professor Mustapha SODQI; Professor Maha SOUSSI ABDALLAOUI; Professor KAMAL MARHOUM EL FILALI (International Journal of Infectious Diseases)
Introduction: Streptococcus pneumoniae is the most frequent and serious cause of bacterial meningitis, currently accounting for 70% of all cases of community-acquired bacterial meningitis, with a case-fatality rate of 17-30%. The purpose of this study was to describe the epidemiological, clinical, bacteriological, therapeutic and evolutionary aspects of purulent Streptococcus pneumoniae meningoencephalitis in adults in Casablanca. Methods: Descriptive study of 13 adults admitted for purulent Streptococcus pneumoniae meningoencephalitis to the infectious diseases department of Ibn Rochd Hospital Center from January 2021 to December 2023. Results: The median age was 40 (interquartile range [IQR]: 19-56) years with a sex ratio (M/F) of 1.6, and 62% (8/13) of patients were male. The most common sites of onset were head trauma with osteomeningeal breach (54%) and ENT infections (31%), and the underlying factor was diabetes mellitus (15%). The clinical manifestations of all patients were meningeal syndrome, infectious syndrome (fever) and encephalitis syndrome (disturbed consciousness and comitiality).The intracranial complication associated with meningitis, hydrocephalus, occurred in 8.8% of cases. CSF was purulent in 9 cases (69%), and cytochemical examination revealed a predominantly neutrophilic pleocytosis with a median count of 1887 elements/mm 3, hyperproteinorachia (IQR: 14±0.74 g/l) and hypoglycorachia (IQR: 1.87±0.049). Bacteriological confirmation was provided by direct examination of CSF (10 cases, 77%) and multiplex PCR (3 cases, 23%). The sensitivity was 100% for ceftriaxone and vancomycin. Ceftriaxone was used as initial monotherapy, and vancomycin was added if the patient's state of consciousness did not improve. All patients were also treated with dexamethasone-based corticosteroids.The case fatality rate was 46%. Disturbed consciousness was the main risk factor for lethality and antibiotic therapy (ceftriaxone and vancomycin). Discussion: The use of empirical vancomycin did not improve mortality rates. Patients in critical condition [1,2] and of advanced age [1,3] die more frequently. The problems of antibiotic resistance and empirical treatment (ceftriaxone and vancomycin) pose a real challenge to the practitioner.The beneficial effects of dexamethasone corticosteroid therapy in adults with pneumococcal meningitis are currently recognized [4,5]. In our case, 46% of patients who died were treated with corticosteroids.Complications of pneumococcal meningitis are dominated by neurological damage, which can be found in 75% of cases when detected systematically by CT and MRI scans [6].Case-fatality rates for pneumococcal meningitis vary according to the age and level of socioeconomic development of the populations studied. In adults, they exceed 50% in developing countries, while in developed countries they are below 30% [1,6,7] Conclusion: Pneumococcal meningoencephalitis is responsible for a high case-fatality rate in developing countries. The introduction of pneumococcal vaccine (adult) into the vaccination schedule should be undertaken with a view to reducing the case-fatality rate of pneumococcal meningoencephalitis.